2002
DOI: 10.1002/ijc.10772
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase‐2A restricts migration of Lewis lung carcinoma cells by modulating the phosphorylation of focal adhesion proteins

Abstract: The process of metastasis requires migration of tumor cells from the primary tumor into the vasculature and the target tissue. 1 Studies with a variety of tumor types have shown that metastatic tumor cells are more highly motile than are nonmetastatic cells. [2][3][4][5] Cellular migration is influenced by the degree of adhesiveness to a substratum, signaling through integrins, and active turnover of focal adhesions. 6,7 There is, however, a fine balance between adherence/detachment and motility. A strong shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…5E). Other investigators have reported that pharmacological inhibition of PP2Ac leads to increased migration of endothelial and carcinoma cells (32,33). Thus, the enhanced ERK1/2 and p38 signaling in PP2Ac ␣ -depleted cells would be predicted to exhibit greater adhesive and migratory properties.…”
Section: Discussionmentioning
confidence: 96%
“…5E). Other investigators have reported that pharmacological inhibition of PP2Ac leads to increased migration of endothelial and carcinoma cells (32,33). Thus, the enhanced ERK1/2 and p38 signaling in PP2Ac ␣ -depleted cells would be predicted to exhibit greater adhesive and migratory properties.…”
Section: Discussionmentioning
confidence: 96%
“…In these cells, there is increased Ser phosphorylation of paxillin and reduced Tyr phosphorylation of paxillin, FAK and Src. PP2A holoenzymes containing the B'/B56γ1 isoform co-localize with, interact with, and dephosphorylate paxillin [14], possibly at Ser-457 and Ser-481 residues [39], the phosphorylation of which is critical for cell migration [39]. In contrast, the regulation of Tyr phosphorylation by PP2A is indirect, and may involve Tyr phosphatases like Shp-2 [40].…”
Section: Pp2a and Cell-matrix Interactionsmentioning
confidence: 99%
“…1). PP2A inhibition induces the disorganization of focal adhesion sites and increases cell migratory activity in endothelial cells [16], non-metastatic Lewis Lung carcinoma (LLC-C8) tumor variants [38][39][40] and keratinocytes [15]. In these cells, there is increased Ser phosphorylation of paxillin and reduced Tyr phosphorylation of paxillin, FAK and Src.…”
Section: Pp2a and Cell-matrix Interactionsmentioning
confidence: 99%
“…Regardless, mutagenesis of the LIM domains that mediate PTP-PEST binding decreases cell adhesion and motility on fibronectin, perhaps indicating a role for paxillin binding to PTP-PEST in focal adhesion dynamics (27, 41). Finally, paxillin also interacts with the serine/threonine phosphatase PP2A, and although it is not known if paxillin is a physiological protein phosphatase 2A substrate, perturbation of this association and consequent increase in paxillin LIM3 serine phosphorylation enhances cell metastasis (110,323).…”
Section: Dephosphorylationmentioning
confidence: 99%